Resistance to Chinese Nine Dotted Line Claim of the Spratly Islands and solution provided by Common Heritage of Mankind - Muhammad Naguib Abdul Malik (Penerbit Universiti Kebangsaan Malaysia, 2015)
The Spratly Islands issue has been contentious for many South East Asian countries (namely Malaysia, Vietnam, Philippines and Brunei) mainly because China claims every inch of the Spratly Islands. The problem is further exacerbated when China has taken steps in claiming her rights upon the Spratly Islands which clearly has caused tensions to run high with its Southeast Asian neighbours. This Article views the solution offered by Common Heritage of Mankind which originated from the Islamic International Law (Siyar) in dealing with the issue of the Spratly Islands.